Role and prospects of green quantum dots in photoelectrochemical hydrogen generation: A review. (12th March 2022) - Ikram, Ashi; Zulfequar, Mohammad; Satsangi, Vibha R.
Abstract: Eco-friendly quantum dots (QDs) can be termed green QDs which stand as an attractive choice to modify the properties of known semiconductors in the direction of getting efficient photoelectrodes for solar-induced photoelectrochemical (PEC) splitting of water, due to their peculiar properties. Thus, it is of high significance to analyze their merit/demerit as an effective scaffold in PEC cell. QDs are known for their excellent optical properties however, the coupling of green QDs with semiconductor is not only useful in improving absorption characteristics but also promotes charge transfer. This review has undertaken the critical analysis on the worldwide research going on the green QDs modified photoelectrode with respect to their optical, electrical & photoelectrochemical properties, role, usefulness, efficiency, and finally the success in PEC system for hydrogen production. Various methods on the facile synthesis & sensitization techniques of green QDs available in the literature have also been discussed. Further, recent advances on the development of green QDs based photo-electrode, along with major challenges of using green QDs in this field have also been presented. Graphical abstract: Image 1 Highlights: Critical assessment on challenges and possible way to deal with green QDs in PEC. Current status of green QDs used in PEC for the development of green technology. Detail out the synthesis/sensitization techniques and properties of green QDs. Discussion on various strategies of green QDs modification.